1999
DOI: 10.1002/(sici)1099-1077(199908)14:6<363::aid-hup125>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

A unifying hypothesis of Alzheimer's disease. I. Ageing sets the stage

Abstract: In a series of ®ve papers, evidence from neurobiology, endocrinology and immunology is integrated into a holistic, coherent hypothesis accommodating genetic, medical and environmental risk factors into a cascade of pathophysiological events that leads to the clinical manifestation of Alzheimer's disease (AD). The perturbation of the calcium-energy-oxidative stress triangle emerges as pathophysiological leitmotif of ageing and AD. Cellular Ca 2 homeostasis and energy metabolism are closely interdependent. Ca 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 678 publications
(521 reference statements)
0
3
0
Order By: Relevance
“…Recent investigations of several AN-1792-vaccinated patients, who survived for extended periods, revealed that all ultimately died with dementia despite an apparent therapy-induced absence of amyloid deposits [1]. The factors that both influence or are influenced by APP processing remain undefined, but may include fundamental energy deficiency [71;72;7779] arising as a consequence of increasing vascular deficiencies [47;49;80], mitochondrial failure [8184] or other stressing mechanisms and co-morbidities associated with aging decay that, in principle, could exert a broad range of synergistic impacts beyond amyloid deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations of several AN-1792-vaccinated patients, who survived for extended periods, revealed that all ultimately died with dementia despite an apparent therapy-induced absence of amyloid deposits [1]. The factors that both influence or are influenced by APP processing remain undefined, but may include fundamental energy deficiency [71;72;7779] arising as a consequence of increasing vascular deficiencies [47;49;80], mitochondrial failure [8184] or other stressing mechanisms and co-morbidities associated with aging decay that, in principle, could exert a broad range of synergistic impacts beyond amyloid deposition.…”
Section: Discussionmentioning
confidence: 99%
“…However, these techniques have not been particularly useful for pharmacology compared to neurochemical techniques [33], with particular reference to the main neurotransmitters identified [31]. For example, according to Schneider [64], the signs of psychosis associated with dementia are highly correlated to a reduction of serotonin levels in the cortex, a major reduction of the cholinergic neurotransmission (notably in the frontotemporal circuits) and to an increase in the number of adrenoceptors in different areas of the brain.…”
Section: Theoretical Basismentioning
confidence: 99%
“…The gonadal hormone-mediated deterioration of the somatic trophic milieu elicits a systemic and cellular metabolic stress response (Heininger 1999). Mitochondria have been shown to be a central key affecting lifespan (Kirkwood and Kowald 1997).…”
Section: Introductionmentioning
confidence: 99%